3-Methylglutaconic Aciduria Type I: A Rare Cause of Late-Onset Leukoencephalopathy. (7th October 2022) - Benzoni, Chiara; Magri, Stefania; Moscatelli, Marco; Fenu, Silvia; Caccia, Claudio; Taroni, Franco; Salsano, Ettore; Di Bella, Daniela
Abstract : A 61-year-old man presented with a 7-year-history of slightly progressive unsteadiness. At neurologic examination, autonomous ataxic-spastic gait and mild executive-attentional dysfunction were present. Brain MRI showed a diffuse leukoencephalopathy (Figure 1) while cerebral 18 FDG-PET and nerve conduction studies were unremarkable. The authors made a diagnosis of 3-methylglutaconic aciduria type 1 (MGCA1, OMIM: 250950) by using a custom leukodystrophy-targeted gene panel which led to the identification of a novel, homozygous pathogenic variant in AUH (c.996_1004delGCCCCCTCG, p.Arg332_Arg335delinsSer). In agreement with the genetic result, the authors subsequently demonstrated a markedly increased urinary excretion of 3-methylglutaconic acid. In fact, the authors had not previously hypothesized the disease for its rarity, and there were neither clinical manifestations (e.g., macrocephaly, psychomotor delay, or learning disabilities) nor neuroimaging findings (e.g., predominantly subcortical white matter abnormalities, widening of the Sylvian fissures, and basal ganglia abnormalities), which could suggest another, more frequent cerebral organic aciduria (e.g., L-2-hydroglutaric aciduria and glutaric acidemia type 1) 2 and justify urinary organic acid screening. The authors also documented the spectroscopy findings characteristic of the disease (Figure 2). 1 Although very rare, 3, 4 MGCA should be considered in the differential diagnosis of late-onset leukoencephalopathy with ataxia and cognitive impairment.